A study of mesoscale air–sea interaction in the Southern Ocean with a regional coupled model. (September 2020) - Perlin, Natalie; Kamenkovich, Igor; Gao, Yu; Kirtman, Ben P.
Abstract: Coupling between the atmosphere and ocean is scale-dependent. For example, in the mid-latitudes and at oceanic mesoscales (spatial scales between 10 and hundreds of kilometers), the air–sea interactions are driven by the oceanic variability, and the atmosphere responds to the changes in the sea surface temperature anomalies (SSTA), which are created by fast oceanic advection. This study explores these interactions, using a regional high-resolution atmosphere–ocean coupled model with a realistic atmospheric component and a semi-idealized oceanic model of a zonal flow. The atmospheric component consists of two nested domains: the inner domain fully coupled with the ocean model, and the outer domain one-way coupled with the observed SST. Two 2-year simulations are discussed here: one in which the oceanic isopycnals are steep and ocean currents are strong ("Strong Currents" or SC) and another with less steep isopycnals and weaker currents ("Weak Currents" or WC). Simulated mesoscale variability occurs on a wide range of spatial scales, and we distinguish large-mesoscale (hundreds of kilometers and shorter) and small-mesoscale (tens of kilometers and shorter) anomalies. The model is most applicable to the mid-latitude Southern Ocean far from any boundaries. Relationships between atmospheric variables and SSTA are studied using temporal correlations and coupling coefficients, and for both large-mesoscale and small-mesoscale anomalies. Significant positive correlations between large-mesoscale anomalies are found for following pairs of variables: equivalent neutral stability (ENS) 10-meter winds and SSTA, wind stress and SSTA, and wind stress divergence/curl and SSTA downwind/crosswind gradients. The temporal correlations are smaller for the small-mesoscale anomalies. The correlation coefficients are also higher for the model SC region, whereas the corresponding coupling coefficients are higher in the model WC region. Among all pairs, the coupling coefficients for the ENS winds and SSTA are the most consistent in time and various environmental conditions. Coupling coefficients for the wind stress and SSTA show a nearly linear dependence on the ENS wind speed. As a result, the reported variability in these coupling coefficients indicates a complex, nonlinear relationship between the wind and SST anomalies. Our numerical analysis indicates strong presence of the Vertical Mixing Mechanism involving the downward momentum mixing on both small- and large-mesoscales. In contrast, the active presence of the Pressure Adjustment Mechanism in the Marine Boundary Layer could not be confirmed on the spatial and time scales considered in this study. Graphical abstract: Highlights: A regional model combines a realistic atmosphere and an idealized ocean component. Two Southern Ocean regions with very different densities and velocities are studied. The relationship between the winds and SST is studied using coupling coefficients. The coupling coefficients depend on the region and scales of the SST anomalies. Vertical Mixing Mechanism is important at both small- and large-mesoscales. The importance of the Pressure Adjustment Mechanism is not confirmed.